Colorectal tumor-related intestinal obstruction: Surgical approaches and treatment strategies (Annals of Medical Research, 2025)
Aim: This study aims to evaluate the treatment approaches and management strategies applied in patients with colon tumor-related intestinal obstruction in colorectal emergencies. The efficacy of treatment methods and the types of surgical interventions based on tumor localization were analyzed.Materials and Methods: A total of 45 patients diagnosed with intestinal obstruction due to colorectal tumors at Erciyes University Department of General Surgery between 01.08.2022 and 01.08.2024 were retrospectively reviewed. The demographic data, tumor localizations, and treatment methods were analyzed.Results: The study included patients with an average age of 65.09 (± 12.65) years, of whom 57.8% were male and 42.2% were female. The most common tumor location was the sigmoid colon (66.7%). Emergency surgery was performed in 91.1% of cases, with tumor resection and stoma creation being the most frequent procedures (70.7%). A significant linear relationship was observed between tumor location and the type of surgical procedure (p=0.019).Conclusion: Surgical intervention is the preferred treatment method for colorectal cancer-related intestinal obstruction. While resection with stoma creation is frequently performed for sigmoid colon tumors, the final treatment strategy depends on both the specific location of the tumor and the overall health of the patient.
Keywords: Colon tumor; Colorectal emergencies; Intestinal obstruction treatment; Surgical intervention; Tumor localization